FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU PEMBERIAN AIR SUSU IBU (ASI) EKSKLUSIF DI WILAYAH KERJA PUSKESMAS PEGANDAN KOTA SEMARANG - Setyorini, Ria Novita; Widjanarko, Bagoes; Sugihantono, Anung (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Exclusive breastfeeding can reduce infant mortality. However, based on reports from January to June 2016, exclusive breastfeeding coverage at Pegandan Health Center was only 7%. Therefore this research aimed to analyze the factors that influence the behavior of exclusive breastfeeding in the working area of Pegandan Health Center Semarang City.This was a quantitative with cross sectional approach research. The samples were using proportional sampling at mothers who had 7-12 months babies. Data were collected by interview using questionnaire. This research used univariate, bivariate, and multivariate analysis.The results of this research showed that majority of respondents aged 26-35 years, housewives and multiparous. 54.2% of respondents did not give exclusive breastfeeding. The chi-square test showed that knowledge (p=0.05) and attitudes toward exclusive breastfeeding (p=0,000) were significantly associated with exclusive breastfeeding. While age (p=0.151), job (p=0.356), parity (p=1,000), maternity place (p=0,723), birth attendant skill (p=0,616), exclusive breastfeeding information (p=0,055) availability of supporting facilities (p=0.638), husband (p=0.428), family (p=0.269), and significant others support (p=0.444) were not significantly associated with exclusive breastfeeding behavior. Binary logistic regression test results show that of all variables, only attitude has significant influence on exclusive breastfeeding behavior (OR = 7,299).It was suggested to optimize Breastfeeding Support Group and dissemination of information through social media as information delivery approaches.